ANALISIS KANDUNGAN GIZI DAN GLUTEN COOKIES TEPUNG MODIFIKASI SINGKONG DENGAN PENAMBAHAN WHEY PROTEIN KONSENTRAT - Febbyandi Isnanda Pandiangan; Veronica; Oei Alvindra Wijaya (Jurnal Pengolahan Pangan, 2022)
Indonesia is one of the largest cassava producers in the world. Cassava can be processed into modified cassava flour (MOCAF) which has many functions. A lot of studies about MOCAF have been conducted to know the potency of replacing wheat flour. One of the popular snack products made from wheat flour is cookies with high protein. This study aimed to see the potential of the MOCAF as a raw material replacing wheat flour to produce low-gluten soft cookies with the addition of concentrated whey protein to increase the protein value. This research used 2 types of formulations, MOCAF: wheat flour (30%:70% and 40%:60%) and the addition of whey protein concentrate with the evaluation of protein content, fat content, water content, and gluten. This study showed that both types of formulations have the potential as a substitute for wheat flour to make soft cookies. All formulations can be claimed to be gluten-free products and the second formulation can almost be claimed to be a source of protein. The resulting cookies have the potential to reduce dependence on wheat flour and can be consumed by consumers who have gluten allergies or have high protein requirements.